2013
DOI: 10.1371/journal.pone.0053757
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Stable, Metronidazole-Resistant Clostridium difficile Clinical Isolate

Abstract: Background Clostridium difficile are Gram-positive, spore forming anaerobic bacteria that are the leading cause of healthcare-associated diarrhea, usually associated with antibiotic usage. Metronidazole is currently the first-line treatment for mild to moderate C. difficile diarrhea however recurrence occurs at rates of 15–35%. There are few reports of C. difficile metronidazole resistance in the literature, and when observed, the phenotype has been transient and lost after storage or exposure of the bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 56 publications
7
80
0
3
Order By: Relevance
“…difficile strains showing resistance to metronidazole are rare, and laboratory manipulation of these strains frequently results in a MIC decrease toward the susceptibility range (4,5). Therefore, the investigation of resistance mechanisms in C. difficile has proved difficult.…”
mentioning
confidence: 99%
“…difficile strains showing resistance to metronidazole are rare, and laboratory manipulation of these strains frequently results in a MIC decrease toward the susceptibility range (4,5). Therefore, the investigation of resistance mechanisms in C. difficile has proved difficult.…”
mentioning
confidence: 99%
“…The development of resistance to metronidazole leading to treatment failure during the course of metronidazole therapy in a patient has been reported (Buta et al, 2010;Soki et al, 2013). Numerous studies have demonstrated the incidence of metronidazole resistance in recent years (Alauzet et al, 2010;Lynch et al, 2013;Abdollahi et al, 2011). In a study conducted by Datta et al (2005) reported that 85% strains of Helicobacter pylori were resistant to metronidazole.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas mechanism for metronidazole resistance in B. fragilis include the presence of nim genes, which encode 5-nitroimidazole reductases that convert metronidazole to a non-toxic amino derivative (Pumbwe et al, 2008), overexpression of the DNA repair protein, RecA (Steffens et al, 2010) and disruption of the electron transport chain (Lynch et al, 2013). 5-nitroimidazole resistance genes, nimA to E, have been identified to confer reduced susceptibility to 5-nitroimidazole antibiotics on species of the B. fragilis group (Hartmeyer et al, 2012).…”
Section: But Comprising Least Common Bacteroides Occur Inmentioning
confidence: 99%
“…For example, the Tn6218 element of C. difficile contains a cfr-like gene that can confer resistance to peptidyl transferase inhibitors such as linezolid 255 and the Tn5397 element carries a tetracycline resistance determinant 256 . Reduced susceptibility or resistance to the commonly used antibiotics vancomycin, metronidazole and fidaxomicin has been noted [257][258][259][260] . Although this is cause for concern, the clinical relevance of resistance to these antibiotics so far is limited.…”
Section: Antibiotic Resistance Of Clostridium Difficilementioning
confidence: 99%